IMPLEMENTASI SUFI HEALING PADA ERA NEW NORMAL PANDEMI COVID-19 DALAM MENJAGA KONDISI HOMEOSTASIS TUBUH MASYARAKAT: Studi Analisis di Desa Kayen Bandarkedungmulyo Jombang Jawa Timur - Muhammad Asrori Ma'sum; Muhammad Nasrul Waton (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2020)
Abstract: This article discusses the use of Sufi healing in the new normal era of the Covid-19 pandemic in maintaining the homeostatic condition of the community in Kayen Village, Bandarkedungmulyo Jombang, East Java. Sufi healing can be interpreted as a model of alternative therapy or physical or psychological healing based on values ??and adopting the practice of Sufism as a means of healing or prevention. Meanwhile, the body's efforts to maintain a stable state of the environment are called Homeostasis which is taken from Greek, namely homeo which means the same and stasis which means maintaining a state which means staying in a healthy condition. With worship activities adapted from the practices of Sufism, carried out by the community in Kayen Village during the new normal Covid-19 pandemic, such as reading the Koran, dhikr, praying, reading prayers that bring calm, increasing one's faith and piety so that it raises relaxation response which has an impact on increasing body immunity. By increasing one's body immunity, it keeps people from disease, viruses, bacteria, or other pathogens, so that a person can maintain a healthy body condition (homeostasis). Although healing requires istiqomahan in carrying out worship practices carried out by someone.